Resin composition, prepreg containing same, copper-clad plate and printed circuit board

Through the combination of maleimide compounds of specific structural formulas, polyphenylene ether resin, crosslinking agent and reactive phosphorus-containing flame retardant, the compatibility and flame retardancy problems of resin materials in high-frequency applications are solved, and the problem of corrosion resistance of resin materials is achieved. The balance of low dielectric loss and high heat resistance improves the overall performance of printed circuit boards.

CN119161544AActive Publication Date: 2024-12-20GUANGDONG SHENGYI SCI TECH

Patent Information

Application Number
CN202310734625.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-20
Publication Date
2024-12-20
Estimated Expiration
2043-06-20

AI Technical Summary

Technical Problem

In high-frequency applications, existing resin materials are difficult to take into account the compatibility of maleimide compounds, halogen-free flame retardant, low dielectric loss and high heat resistance, resulting in poor dielectric performance and thermal expansion characteristics, affecting PCB Processing and reliability.

Method used

By designing a combination of maleimide compounds with specific structural formulas, polyphenylene ether resin, crosslinking agent and reactive phosphorus-containing flame retardant, the dosage of each component is controlled, the resin crosslinking reaction is realized, and the crosslinking density is improved. Glass transition temperature reduces the thermal expansion coefficient and enhances flame retardant performance.

Benefits of technology

Halogen-free flame retardant, low dielectric loss and high heat resistance are achieved, dielectric performance and low thermal expansion characteristics are balanced, comprehensive performance of resin composition is improved, and printed circuit boards are suitable for high-frequency applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004295386500000031
    Figure BDA0004295386500000031
  • Figure BDA0004295386500000032
    Figure BDA0004295386500000032
  • Figure BDA0004295386500000051
    Figure BDA0004295386500000051
Patent Text Reader

Abstract

The invention provides a resin composition, a prepreg containing the resin composition, a copper-clad plate and a printed circuit board. The resin composition is prepared from the following raw materials in parts by weight: 30-50 parts of a maleimide compound, 20-40 parts of polyphenyl ether resin, 10-20 parts of a cross-linking agent, 5-15 parts of a reactive phosphorus-containing flame retardant and 60-150 parts of an inorganic filler, wherein the total weight part of the maleimide compound, the polyphenyl ether resin, the cross-linking agent and the reactive phosphorus-containing flame retardant is 100 parts, and the resin composition is prepared from the following components in parts by weight: 30-50 parts of the maleimide compound, 20-40 parts of the polyphenyl ether resin, 10-20 parts of the cross-linking agent, 5-15 parts of the reactive phosphorus-containing flame retardant and 60-150 parts of the inorganic filler. The resin composition provided by the invention realizes the characteristics of halogen-free flame retardance and low dielectric loss, can well balance the dielectric property, low thermal expansion and high heat resistance, and has excellent comprehensive performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of printed circuits, and in particular relates to a resin composition, a prepreg containing the same, a copper clad laminate and a printed circuit board. Background Art

[0002] With the high performance and multi-function of electronic products, their electronic devices are more highly integrated and high-density, and the high frequency of transmission signals requires the substrate material to have a low dielectric constant and low dielectric loss tangent to reduce the damping effect on the electrical signal, thereby increasing the signal transmission speed and reducing the signal transmission loss; with the increase in signal frequency and the increase in signal processing, not only is the plate required to have good dielectric properties, but in order to avoid reliability problems caused by inconsistent thermal expansion between PCB and chip, the substrate material is also required to have the characteristic of low thermal expansion.

[0003] As a low-polarity, cross-linkable resin, thermosetting polyphenylene ether resin is widely used in copper-clad laminates for high-frequency applications due to its low dielectric constant and low dielectric loss factor. In order to improve the heat resistance and reliability of polyphenylene ether materials, maleimide compounds with high temperature resistance are often introduced into the resin material to increase its glass transition temperature and reduce thermal expansion, thereby increasing heat resistance. As the requirements for heat resistance and reliability of high-frequency materials continue to increase, the amount of maleimide compounds used is also increasing. However, due to the relatively large polarity of maleimide compounds and poor solubility in low-polarity solvents, there are compatibility issues with polyphenylene ether resins and polyolefin resins. The glue will produce resin precipitation, thereby affecting the cross-linking of the resin and the performance of the board. Improving the compatibility of maleimide compounds has become the key to the use of resins.

[0004] With the halogen-free trend of electronic materials, low-polarity phosphorus-containing flame retardants are often introduced to balance low dielectric loss and halogen-free flame retardancy. These flame retardants are mostly dispersed into the resin system in the form of organic fillers, which leads to problems such as decreased fluidity and adhesion of the resin, seriously affecting the processing and application reliability of PCBs. Therefore, suitable flame retardants are an issue that must be considered for halogen-free materials in high-frequency applications.

[0005] CN109096262A discloses a vinyl-modified maleimide compound, which utilizes 4-vinylbenzylamine to modify maleimide to obtain a styrene-terminated polyamine-imide resin, which is used in conjunction with a cross-linking agent. Although this structure can improve the solubility of the bismaleimide compound, the presence of the NH bond leads to a significant increase in the water absorption of the resin and poor dielectric properties.

[0006] TW202041591A discloses a composition of a maleimide compound containing an indane skeleton and a diene polymer, but the resin disclosed therein cannot achieve a flame retardant effect among diene polymers.

[0007] CN105936745A discloses a resin composition, in which a dibenzyl-type bis-DOPO flame retardant is introduced into a system of olefin-terminated polyphenylene ether (PPO), butadiene-styrene resin and bismaleimide resin. However, as an organic filler, its addition will lead to a decrease in resin fluidity and poor adhesion.

[0008] Therefore, how to provide a resin composition that has good compatibility with maleimide compounds, can achieve halogen-free flame retardancy and low dielectric loss properties, and can better balance dielectric properties, low thermal expansion and high heat resistance, and has excellent comprehensive performance has become a technical problem that needs to be solved urgently. Summary of the invention

[0009] In view of the deficiencies in the prior art, the object of the present invention is to provide a resin composition, a prepreg, a copper clad laminate and a printed circuit board comprising the same. In the present invention, by designing the specific composition of the resin composition, the prepared resin composition achieves halogen-free flame retardancy and low dielectric loss characteristics while solving the compatibility of maleimide compounds, and can better balance dielectric properties, low thermal expansion and high heat resistance, and has excellent comprehensive performance.

[0010] To achieve this object, the present invention adopts the following technical solutions:

[0011] In a first aspect, the present invention provides a resin composition, wherein the total weight of the maleimide compound, the polyphenylene ether resin, the crosslinking agent and the reactive phosphorus-containing flame retardant is 100 parts, and the raw materials for preparing the resin composition include the following components in parts by weight:

[0012]

[0013] The maleimide compound includes a maleimide compound having the following formula M-1;

[0014]

[0015] Wherein, in formula M-1, n represents an integer of 2-10 (for example, it can be 2, 3, 4, 5, 6, 7, 8, 9 or 10);

[0016] In formula M-1, R 1 , R 2 , R 3 With R 4 Each independently represents a C1-C5 alkyl group (for example, a methyl group, an ethyl group, a propyl group, a butyl group or a pentyl group) or a phenyl group, and R 1 With R 2 The difference in the number of carbon atoms between them is ≥ 2 (for example, it can be 2, 3, 4 or 5), R 3 With R4 The difference in the number of carbon atoms between the two is ≥ 2 (for example, it can be 2, 3, 4 or 5).

[0017] In the present invention, a maleimide compound is used to undergo a crosslinking reaction with a low-polarity polyphenylene ether containing crosslinkable unsaturated double bonds, a crosslinking agent and a reactive phosphorus-containing flame retardant. In addition, the polyphenylene ether resin and the crosslinking agent self-polymerize and react with each other, thereby increasing the rigid imide structure in the system and improving the crosslinking density of the resin. The cured product thus obtained has the characteristics of low dielectric constant, low dielectric loss tangent, high glass transition temperature (Tg) and low coefficient of thermal expansion (CTE).

[0018] The common maleimide compounds are difficult to dissolve in low polar solvents such as toluene due to their symmetrical structure and high polarity. They have poor compatibility with low polar polyphenylene ether or polyolefin resins. After the mixed resin is cured, there is a phase separation phenomenon, which affects the comprehensive performance of the cured resin. It has been found that in the benzene ring structure of the maleimide compound, an asymmetric substituent (that is, R in Formula M-1) is used. 1 With R 2 The difference in the number of carbon atoms between them is ≥ 2, R 3 With R 4 The difference in the number of carbon atoms between the two is ≥2), and the number of benzene ring structures containing asymmetric substituents is at least 3 or more (that is, n≥2 in formula M-1), which can not only enhance the solubility of the maleimide compound in non-polar solvents and improve its compatibility with polyphenylene ether and polyolefin resins; but also, due to the steric effect, the reaction temperature of the maleimide compound with the imide ring double bond and the unsaturated double bond of olefin or polyphenylene ether will be higher and the reaction will be slower, thereby making the overall reaction of the system relatively synchronous and avoiding the phase separation phenomenon.

[0019] In the present invention, based on the resin system with a total weight of 100 parts by weight of maleimide compound, polyphenylene ether resin, crosslinking agent and reactive phosphorus-containing flame retardant, the addition amount of maleimide compound is preferably 30-50 parts by weight. When it is less than 30 parts by weight, the heat resistance of the resin composition is insufficient; when it exceeds 50 parts by weight, the water absorption rate of the resin composition is too large, affecting its electrical properties. The polyphenylene ether resin is preferably 20-40 parts by weight. When it is less than 20 parts by weight, the heat resistance of the resin composition is insufficient; when it exceeds 40 parts by weight, the apparent quality of the bonding sheet of the resin composition is not good. The crosslinking agent is mainly used to increase the crosslinking density of the copolymer, increase the density of the crosslinking network, and improve the glass transition temperature and heat resistance of the material. The addition amount of the crosslinking agent is preferably 10-20 parts by weight. When it is less than 10 parts by weight, the crosslinking degree of the resin composition is low and the heat resistance is limited; when it exceeds 20 parts by weight, the bonding sheet of the resin composition becomes soft and easy to stick. The addition amount of the reactive phosphorus-containing flame retardant is preferably 5-15 parts by weight. If it is less than 5 parts by weight, the flame retardant effect of the resin composition is poor; if it exceeds 15 parts by weight, the glass transition temperature of the resin composition is low and the heat resistance is insufficient.

[0020] In the present invention, based on the total weight of the maleimide compound, the polyphenylene ether resin, the crosslinking agent and the reactive phosphorus-containing flame retardant as 100 parts, the weight of the maleimide compound can be 30 parts, 32 parts, 34 parts, 36 parts, 38 parts, 40 parts, 42 parts, 44 parts, 46 parts, 48 ​​parts or 50 parts, etc.

[0021] The weight proportions of the polyphenylene ether resin may be 20 parts, 22 parts, 24 parts, 26 parts, 28 parts, 30 parts, 32 parts, 34 parts, 36 parts, 38 parts or 40 parts, etc.

[0022] The weight proportions of the cross-linking agent may be 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts or 20 parts, etc.

[0023] The weight proportions of the reactive phosphorus-containing flame retardant may be 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts or 15 parts, etc.

[0024] The weight proportion of the inorganic filler may be 60 parts, 70 parts, 80 parts, 90 parts, 100 parts, 110 parts, 120 parts, 130 parts, 140 parts or 150 parts, etc.

[0025] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the objectives and beneficial effects of the present invention can be better achieved and realized.

[0026] As a preferred technical solution of the present invention, the maleimide compound also includes maleimide compounds having the following formula M-2, formula M-3, and formula M-4;

[0027]

[0028] Wherein, in Formula M-2 and Formula M-3, n each independently represents an integer of 1-10 (for example, 1, 2, 3, 4, 5, 6, 7, 8, 9 or 10);

[0029] As a preferred technical solution of the present invention, the mass percentage of the maleimide compound of formula M-1 is ≥30%, for example, it can be 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85% or 90%, etc. Preferably, the mass percentage of the maleimide compound of formula M-1 is ≥60%, and the mass percentage of formula M-1 is high, so that the compatibility of the system is better. In the present invention, based on the resin system with a total weight of 100 parts of maleimide compound, polyphenylene ether resin, crosslinking agent and reactive phosphorus-containing flame retardant, the addition amount of maleimide compound is 30-50 parts by weight, which means that the weight of all maleimide compounds is 30-50 parts by weight.

[0030] The maleimide compound of formula M-1 can be used alone or in combination with any one or at least two of the maleimide compounds of formula M-2, formula M-3 or formula M-4. The combined use can make up for the shortcomings of using a single maleimide compound. In order to avoid incompatibility problems, when the maleimide compound of formula M-1 is compounded with the other three maleimide compounds, the mass percentage of the maleimide compound of formula M-1 in the maleimide compound should be 30% or more.

[0031] Maleimide compounds conforming to formula M-1 include, but are not limited to, DFE950A of Dongcai Technology Co., Ltd. (as shown in the following formula:

[0032]

[0033] Among them, R 1 and R 3 is methyl, R 2 and R 4is propyl, n represents an integer of 2-10); maleimide compounds of formula M-2 exemplarily include but are not limited to: BMI-50P of KI Company and BMI2300 of Yamato Chemical; maleimide compounds of formula M-3 exemplarily include but are not limited to: MIR-3000 of Chemical Pharmaceutical Company; maleimide compounds of formula M-4 exemplarily include but are not limited to: BMI-70 of KI Company and BMI-5100 of Yamato Chemical Company.

[0034] As a preferred technical solution of the present invention, the polyphenylene ether resin includes a polyphenylene ether resin having an unsaturated double bond structure.

[0035] Preferably, the polyphenylene ether resin has a structure as shown in the following formula I:

[0036]

[0037] Wherein, n represents an integer of 1-15 (for example, it may be 1, 2, 5, 7, 9, 10, 12, 14 or 15, etc.), and m represents an integer of 1-15 (for example, it may be 1, 3, 4, 6, 8, 11, 13 or 15, etc.);

[0038] Y represents -C(CH 3 ) 2 -、-CH(CH 3 )-、-CH 2 -、 At least one of;

[0039] X and Z each independently represent at least one of vinyl, styryl, propenyl, vinylbenzyloxy, methacryloxy or allyl;

[0040] R 1 -R 8 Each independently represents hydrogen or methyl.

[0041] Preferably, the number average molecular weight of the polyphenylene ether resin is 1000-4000 g / mol, for example, 1000 g / mol, 1500 g / mol, 2000 g / mol, 2500 g / mol, 3000 g / mol, 3500 g / mol or 4000 g / mol.

[0042] When the number average molecular weight of the polyphenylene ether resin is less than 1000 g / mol, the reaction speed of the polyphenylene ether resin is too fast and difficult to control, and the dielectric properties of the formed resin composition deteriorate; when the number average molecular weight of the polyphenylene ether resin is greater than 4000 g / mol, the melt viscosity of the polyphenylene ether resin is too high, and the compatibility with other resins deteriorates, and the prepared resin composition is prone to poor appearance.

[0043] In the present invention, the molecular weight (weight average molecular weight, number average molecular weight, etc.) is measured according to GB / T21863-2008 and is obtained by gel permeation chromatography (GPC) based on polystyrene calibration.

[0044] As a preferred technical solution of the present invention, the crosslinking agent is selected from any one or a combination of at least two of divinylbenzene, divinylbenzyl ether, 1,2-bis(vinylphenyl)ethane, triallyl isocyanurate, triallyl cyanurate, cyanate ester, 1,2,4-trivinylcyclohexane, tricyclodecane dimethanol dimethacrylate, trimethylolpropane trimethacrylate or a polyolefin resin containing a butadiene structure, wherein typical but non-limiting combinations include: for example, a combination of divinylbenzene and divinylbenzyl ether, a combination of 1,2-bis(vinylphenyl)ethane, triallyl isocyanurate and triallyl cyanurate, a combination of 1,2,4-trivinylcyclohexane, tricyclodecanediol methyl methacrylate, trimethylolpropane trimethacrylate and a polyolefin resin containing a butadiene structure, and the like.

[0045] Preferably, the inorganic filler is selected from any one or a combination of at least two of crystalline silica, synthetic silica, spherical silica, fused silica, hollow silica, chemical spherical silica, aluminum nitride, boron nitride, silicon nitride, silicon carbide, aluminum oxide, magnesium oxide, titanium dioxide, barium titanate, strontium titanate, talc, magnesium carbonate, barium sulfate, calcium carbonate or aluminum borate.

[0046] With the halogen-free electronic materials, inactive phosphorus-containing additives are introduced into the resin system to achieve flame retardant effect, which has different degrees of negative impact on the resin fluidity, adhesion or heat resistance of the product, thereby affecting PCB processing and application reliability; the use of reactive phosphorus-containing flame retardants is compatible with the resin system and can participate in molecular cross-linking reactions, thus avoiding the drawbacks mentioned above.

[0047] As a preferred technical solution of the present invention, the reactive phosphorus-containing flame retardant is a cyclophosphazene resin having unsaturated double bonds.

[0048] Preferably, the reactive phosphorus-containing flame retardant comprises allyl cyclotriphosphazene and / or styryl cyclophosphazene.

[0049] Preferably, the structural formula of the styryl cyclophosphazene is as follows:

[0050]

[0051] Wherein, n represents 3 or 4, the ratio of l to m is 1:1 to 3:1 (for example, it can be 1:1, 1.2:1, 1.4:1, 1.6:1, 1.8:1, 2:1, 2.2:1, 2.4:1, 2.6:1, 2.8:1 or 3:1, etc.), and the ratio of l to m is more preferably 3:1, for example: FP-700TP (Fushimi Pharmaceutical Co., Ltd., Japan).

[0052] As a preferred technical solution of the present invention, the resin composition also includes additives.

[0053] It should be noted that the present invention does not have any special restrictions on the specific amount of additives, and the additives can be added according to the type and needs of the additives.

[0054] Preferably, the additive includes any one of a surfactant, an emulsifier, a toughening agent, a viscosity modifier, a pigment, and a hardening accelerator, or a combination of at least two of them, wherein typical but non-limiting combinations include: a combination of an emulsifier and a surfactant, a combination of a toughening agent, a hardening accelerator and a pigment, a combination of a surfactant, an emulsifier, a toughening agent, a viscosity modifier, a pigment, and a hardening accelerator, etc.

[0055] In order to promote the reaction of the resin composition, enhance the crosslinking density, and improve the glass transition temperature and heat resistance, a hardening accelerator may be used to further accelerate the reaction.

[0056] The hardening accelerator is preferably an organic peroxide free radical initiator, further selected from di-tert-butyl peroxide, dilauroyl peroxide, dibenzoyl peroxide, isopropyl peroxyneodecanoate, tert-butyl peroxyneodecanoate, tert-butyl peroxypivalate, tert-butyl peroxyisobutyrate, tert-butyl peroxy-3,5,5-trimethylhexanoate, tert-butyl peroxyacetate, tert-butyl peroxybenzoate, 1,1-di-tert-butyl peroxy-3,5,5-trimethylcyclohexane, 1,1-di-tert-butyl peroxycyclohexane, 2,2-di(tert-butylperoxy)butane, bis(4-tert-butylcyclohexyl)peroxydicarbonate, hexadecyl peroxydicarbonate , tetradecyl peroxydicarbonate, dipentyl peroxide, diisopropylbenzene peroxide, bis(tert-butylperoxyisopropyl)benzene, 2,5-dimethyl-2,5-di-tert-butylperoxyhexane, 2,5-dimethyl-2,5-di-tert-butylperoxyhexyne, diisopropylbenzene hydroperoxide, isopropylbenzene hydroperoxide, tert-amyl hydroperoxide, tert-butyl hydroperoxide, tert-butyl peroxide isopropylbenzene, diisopropylbenzene hydroperoxide, tert-butyl peroxycarbonate-2-ethylhexanoate, tert-butyl peroxycarbonate-2-ethylhexanoate, n-butyl 4,4-di(tert-butylperoxy)valerate, methyl ethyl ketone peroxide or cyclohexane peroxide, or any one or a combination of at least two thereof.

[0057] The resin composition further includes a solvent.

[0058] In the present invention, there is no special limitation on the specific selection of solvents, which illustratively include but are not limited to: ketones such as acetone, butanone, methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone, etc., aromatic hydrocarbons such as toluene, xylene, mesitylene, etc., esters such as ethoxyethyl acetate, ethyl acetate, etc., N,N-dimethylformamide, N,N-dimethylacetamide, N-methyl-2-pyrrolidone, etc. Nitrogen-containing solvents. The above solvents can be used alone or in combination of two or more, preferably aromatic hydrocarbon solvents such as toluene, xylene, mesitylene, etc. are mixed with ketone solvents such as acetone, butanone, methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone, etc.

[0059] The amount of the solvent used can be selected by those skilled in the art based on their own experience, so that the obtained resin glue reaches a viscosity suitable for use.

[0060] In the process of dissolving or dispersing the resin composition in the solvent as described above, an emulsifier may be added. The powder filler and the like may be dispersed evenly in the adhesive solution by dispersion with the emulsifier.

[0061] In a second aspect, the present invention provides a prepreg, comprising a reinforcing material and the resin composition as described in the first aspect.

[0062] Preferably, the resin composition is attached to the reinforcing material by impregnation and drying.

[0063] In a third aspect, the present invention provides a copper clad laminate comprising at least one prepreg as described in the second aspect.

[0064] In a fourth aspect, the present invention provides a printed circuit board, wherein the printed circuit board comprises at least one copper clad laminate as described in the third aspect.

[0065] Compared with the prior art, the present invention has the following beneficial effects:

[0066] The present invention designs the specific composition of the resin composition, further cooperates with a maleimide compound with a specific structural formula and a polyphenylene ether resin, a crosslinking agent and a reactive phosphorus-containing flame retardant, and controls the dosage of the maleimide compound, the polyphenylene ether resin, the crosslinking agent and the reactive phosphorus-containing flame retardant within a specific range. The prepared resin composition has halogen-free flame retardancy and low dielectric loss characteristics, can better balance dielectric properties, low thermal expansion and high heat resistance, and has excellent comprehensive performance. DETAILED DESCRIPTION

[0067] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0068] The component codes and their corresponding component names in the specific implementation mode of the present invention are as follows:

[0069] (A-1) Maleimide compound: DFE950A (Sichuan Dongcai Technology Co., Ltd.);

[0070] (A-2) Maleimide compound: BMI2300 (Yamato Chemical Co., Ltd.);

[0071] (A-3) Maleimide compound: MIR-3000 (Nippon Kayaku Chemical Co., Ltd.);

[0072] (A-4) Maleimide compound: BMI-70 (KI Company);

[0073] (B-1) Methacryloyl-terminated polyphenylene ether resin: SA9000 (Sabic);

[0074] (B-2) Styrene-terminated polyphenylene ether resin: OPE-2st 2200 (Mitsubishi Chemical Corporation);

[0075] (C-1) Triallyl isocyanurate: TAIC (Hunan Fangruida Technology Co., Ltd.);

[0076] (C-2) tricyclodecane dimethanol dimethacrylate: DCP (Shin-Nakamura Chemical Co., Ltd.);

[0077] (D-1) Allyl-containing phosphazene resin: SPV-100 (Otsuka Chemical Co., Ltd.);

[0078] (D-2) Phosphazene resin containing styrene groups: FP-700TP (Fushimi Pharmaceutical Co., Ltd.);

[0079] (D-3) Non-reactive phosphazene: SPB-100 (Otsuka Chemical Co., Ltd.);

[0080] (E) Curing accelerator: Perkadox BC-FF (AkzoNobel);

[0081] (F) Filler: fused silica (Lianrui New Materials Co., Ltd.);

[0082] (G) Glass fiber cloth: 2116E-glass fiber cloth (Shanghai Honghe Electronic Materials Co., Ltd.);

[0083] (H) Electrolytic copper foil: Mitsui Metals Co., Ltd.

[0084] Examples 1-8 and Comparative Examples 1-6

[0085] Examples 1-8 and Comparative Examples 1-6 provide a resin composition and a copper clad laminate, respectively. The components of the resin composition and their amounts (by weight) are shown in Table 1 and Table 2 below:

[0086] Table 1

[0087]

[0088]

[0089] Table 2

[0090]

[0091]

[0092] The preparation method of the copper clad laminate comprises the following steps:

[0093] (1) Glue mixing

[0094] Add 60 parts of toluene and 30 parts of butanone according to the dosage ratio of each component in the above table, stir mechanically for 4 hours to dissolve and mature, and mix into glue.

[0095] (2) Prepreg preparation

[0096] The 2116E-glass fiber cloth was pre-impregnated in the glue obtained in step (1), and part of the liquid resin was removed by a roller clamp to control the resin on the glass fiber cloth to about 65%, and then the glass fiber cloth was dried in an oven at a temperature of 145° C. for 4.5 minutes to obtain the prepreg.

[0097] (3) Preparation of copper clad laminate

[0098] Prepare 2 sheets of electrolytic copper foil with a thickness of 18 μm, stack 5 sheets of prepreg obtained in step (2) with the four sides neatly stacked, and cover the upper and lower surfaces of the stack with a prepared electrolytic copper foil respectively, put them into a laminator, and perform lamination under the following conditions:

[0099] Heat the laminator to 90°C and apply full pressure at 30kgf / cm 2 ; Continue to heat up, and when it reaches 120°C, the material temperature rise rate is controlled at 2°C / min, until 220°C, and maintain for 120min, and solidify to obtain the copper clad laminate.

[0100] Performance Testing

[0101] The copper clad laminates provided in Examples 1-8 and Comparative Examples 1-6 were tested according to the following requirements:

[0102] (1) Glass transition temperature (Tg, °C) of the sheet material: measured by dynamic mechanical analysis (DMA) according to the DMA method specified in IPC-TM-6502.4.24.4.

[0103] (2) Dielectric constant (Dk) and dielectric loss tangent (Df): measured at 10 GHz using the separated dielectric pillar resonator (SPDR) method in accordance with the method specified in IPC-TM-650 2.5.5.13.

[0104] (3) Z-axis CTE and post-Tg CTE: The test is performed using thermomechanical analysis (TMA) according to the method specified in IPC-TM-650 2.4.24, where the Z-axis CTE value is the thermal expansion coefficient of 50-260°C, and the post-Tg CTE is the thermal expansion coefficient from TMA Tg to 260°C.

[0105] (4) Flame retardancy: Test and classify according to the material flammability method specified in UL-94.

[0106] The performance test results are shown in Table 1 and Table 2 above.

[0107] As can be seen from the above content, in the present invention, by designing the specific composition of the resin composition, further by the coordination of a maleimide compound having a specific structural formula with a polyphenylene ether resin, a crosslinking agent and a reactive phosphorus-containing flame retardant, and controlling the amount of the maleimide compound, the polyphenylene ether resin, the crosslinking agent and the reactive phosphorus-containing flame retardant within a specific range, the prepared resin composition has halogen-free flame retardancy and low dielectric loss characteristics, and can better balance dielectric properties, low thermal expansion and high heat resistance, and has excellent comprehensive performance. Its flame retardant grade is V-0, the dielectric constant Dk≤3.99, specifically 3.82~3.99, the dielectric loss tangent value ≤0.0046, specifically 0.0043~0.0046, the Z-axis CTE≤1.42%, specifically 0.93%~1.42%, and the CTE after Tg≤120ppm / ℃, specifically 84~120ppm / ℃.

[0108] It can be seen from Examples 1-8 and Comparative Examples 1-2 that in the present invention, by controlling the amount of maleimide compound, polyphenylene ether resin, crosslinking agent and reactive phosphorus-containing flame retardant within a specific range, the thermal expansion performance of the resin composition can be further reduced and its comprehensive performance can be improved.

[0109] By comparing Example 2 with Comparative Example 3, and Example 1 with Comparative Example 5, it can be seen that if the amount of the maleimide compound in the resin composition is too much (Comparative Example 3), the dielectric properties of the prepared resin composition are poor, the glass transition temperature deteriorates, and at the same time, it has high thermal expansion; if the amount of the maleimide compound in the resin composition is too little (Comparative Example 5), the comprehensive performance of the prepared resin composition is poor, especially the dielectric performance is poor.

[0110] It can be seen from Example 4 and Comparative Example 4 that if the amount of filler in the resin composition is too much (Comparative Example 4), the dielectric properties of the prepared resin composition are poor.

[0111] It can be seen from Example 3 and Comparative Example 6 that if symmetrical maleimide compounds are used to prepare the resin composition (Comparative Example 6), the components of the prepared resin composition are incompatible with each other and cannot be used; it can be seen from Example 3 and Comparative Example 8 that although the benzene ring substituents in the maleimide compound used in Comparative Example 8 are asymmetric, the difference in the number of carbon atoms of the substituents is only 1, and it only contains 2 benzene ring groups with asymmetric substituents, which has poor solubility in solvents. When added to 50 parts by weight, the prepared resin composition also has incompatibility problems and cannot be used.

[0112] It can be seen from Example 1 and Comparative Example 7 that if non-reactive phosphazene is used as a flame retardant, the glass transition temperature of the product decreases significantly and the thermal expansion coefficient increases.

[0113] In summary, the present invention cooperates with a maleimide compound having a specific structural formula and a polyphenylene ether resin, a cross-linking agent and a reactive phosphorus-containing flame retardant, and controls the dosage of the maleimide compound, the polyphenylene ether resin, the cross-linking agent and the reactive phosphorus-containing flame retardant within a specific range. The prepared resin composition has halogen-free flame retardancy and low dielectric loss characteristics, and can better balance dielectric properties, low thermal expansion and high heat resistance, and has excellent comprehensive performance.

[0114] The applicant declares that the present invention illustrates the detailed process flow of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed process flow, that is, it does not mean that the present invention must rely on the above-mentioned detailed process flow to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A resin composition, characterized in that Based on 100 parts by weight of the total weight of the maleimide compound, the polyphenylene ether resin, the crosslinking agent and the reactive phosphorus-containing flame retardant, the raw materials for preparing the resin composition include the following components in parts by weight: The maleimide compound includes a maleimide compound having the following formula M-1; Wherein, in formula M-1, n represents an integer of 2-10; In formula M-1, R1, R2, R3 and R4 each independently represent a C1-C5 alkyl group or a phenyl group, and the difference in the number of carbon atoms between R1 and R2 is ≥2, and the difference in the number of carbon atoms between R3 and R4 is ≥2.

2. The resin composition according to claim 1, characterized in that The maleimide compounds also include maleimide compounds having the following formula M-2, formula M-3, and formula M-4; In Formula M-2 and Formula M-3, n each independently represents an integer of 1 to 10.

3. The resin composition according to claim 1 or 2, characterized in that Taking the mass percentage of the maleimide compound as 100%, the mass percentage of the maleimide compound of formula M-1 is ≥30%, preferably ≥60%.

4. The resin composition according to any one of claims 1 to 3, characterized in that The polyphenylene ether resin includes a polyphenylene ether resin having an unsaturated double bond structure; Preferably, the polyphenylene ether resin has a structure as shown in the following formula I: Wherein, n represents an integer from 1 to 15, and m represents an integer from 1 to 15; Y represents -C(CH3)2-, -CH(CH3)-, -CH2-, At least one of; X and Z each independently represent at least one of vinyl, styryl, propenyl, vinylbenzyloxy, methacryloxy or allyl; R1-R8 each independently represents hydrogen or methyl; Preferably, the number average molecular weight of the polyphenylene ether resin is 1000-4000 g / mol.

5. The resin composition according to any one of claims 1 to 4, characterized in that The crosslinking agent is selected from any one or a combination of at least two of divinylbenzene, divinylbenzyl ether, 1,2-bis(vinylphenyl)ethane, triallyl isocyanurate, triallyl cyanurate, cyanate ester, 1,2,4-trivinylcyclohexane, tricyclodecane dimethanol dimethacrylate, trimethylolpropane trimethacrylate or a polyolefin resin containing a butadiene structure; Preferably, the inorganic filler is selected from any one or a combination of at least two of crystalline silica, synthetic silica, spherical silica, fused silica, hollow silica, chemical spherical silica, aluminum nitride, boron nitride, silicon nitride, silicon carbide, aluminum oxide, magnesium oxide, titanium dioxide, barium titanate, strontium titanate, talc, magnesium carbonate, barium sulfate, calcium carbonate or aluminum borate.

6. The resin composition according to any one of claims 1 to 5, characterized in that The reactive phosphorus-containing flame retardant is a cyclophosphazene resin having unsaturated double bonds; Preferably, the reactive phosphorus-containing flame retardant comprises allyl cyclotriphosphazene and / or styryl cyclophosphazene; Preferably, the structural formula of the styryl cyclophosphazene is as follows: Wherein, n represents 3 or 4, and the ratio of l to m is 1:1 to 3:

1. Preferably, the ratio of l to m is 3:

1.

7. The resin composition according to any one of claims 1 to 6, characterized in that The resin composition further includes an additive; Preferably, the additive includes any one of a surfactant, a toughening agent, a hardening accelerator, a pigment or a viscosity modifier, or a combination of at least two thereof.

8. A prepreg, characterized in that: The prepreg comprises a reinforcing material and a resin composition as claimed in any one of claims 1 to 7; Preferably, the resin composition is attached to the reinforcing material by impregnation and drying.

9. A copper clad laminate, characterized in that: The copper clad laminate comprises at least one prepreg as claimed in claim 8.

10. A printed circuit board, characterized in that: The printed circuit board includes at least one copper clad laminate as claimed in claim 9.

Citation Information

Patent Citations

  • Resin composition

    CN105936745A

  • Vinyl-modified maleimide, composition and article made thereby

    CN109096262A

  • Curable resin composition

    TW202041591A

  • Low dielectric resin composition and preparation method thereof

    CN110218436A

  • Halogen-free flame-retardant resin composition and application thereof

    CN114672168A

Cited By

  • Low-dielectric low-loss resin composition and product and preparation method thereof

    CN120775274A

  • Polymaleimide-triazine resin and preparation method thereof

    CN121108501A

  • Polyphenyl ether with ultralow thermal expansion performance and preparation method thereof

    CN121930462A